The effect of peat and iron supplements on the severity of potato common scab and bacterial community in tuberosphere soil - Sarikhani, Ensyeh; Ságová-Marečková, Markéta; Omelka, Marek; Kopecký, Jan (FEMS microbiology ecology, 2017)
The control of common scab (CS) of potatoes includes resistant cultivars, specific fertilization, increase of soil moisture and chemical treatments. Yet, these management practices do not have common or reproducible results at differing sites. In order to determine the effects of soil organic matter, iron and pH on CS development, peat and DTPA-chelated iron were supplemented to pots filled with soil conducive for CS. All results were compared with the same data obtained for a suppressive soil, which has naturally low severity of CS and occurs nearby. Bacteria, Actinobacteria and the txtB genes from the biosynthetic cluster of thaxtomin, which is responsible for the disease development, were quantified by qPCR in tuberosphere soil and potato periderm. Illumina amplicon sequencing of bacterial 16S rRNA genes was performed for tuberosphere soils. Both peat and iron supplements controlled potato scab, and the combination of the two supplements reduced CS most effectively. The bacterial community was modified by all treatments but the highest number of operational taxonomic units (OTUs) changed towards the suppressive soil after the combined peat and iron treatment. It seemed that iron supplement supported plant defense while both iron and peat additions changed the bacterial community in favor of CS suppression.
Keywords: půdní mikrobiologie; biodiverzita; nemoci rostlin; Solanum tuberosum; Soil; půda; Bacteria; Iron; železo; Plant Diseases; Biodiversity; Soil Microbiology